Qualitative Phytochemical Screening, Fatty Acid Composition Analysis and Biological Studies of Trianthema portulacastrum L. Leaves - Chowdhury, Vaskar; Shristy, Nusrat Tabassum; Rahman, Md Hasanur; Chowdhury, Tofail Ahmad (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Trianthema portulacastrum L. commonly known as ‘horse purslane’ and locally called ‘shvetapunarnava’ is an annual broadleaf plant of tropical areas throughout the world. In this study, determination of moisture and ash content of the plant leaves, as well as qualitative phytochemical test, cytotoxicity assay, antimicrobial activity, fatty acid composition, total phenolic content, total flavonoid content, total antioxidant capacity, and DPPH radical scavenging activity were carried out. Methanol extract of T. portulacastrum leaves was partitioned using Kupchan's method with different solvents of increasing polarity (n-hexane, dichloromethane, chloroform, ethyl acetate). The moisture and ash contents of the leaves were (81.74±0.49)% and (31.05±1.36)%, respectively. Initial phytochemical screening of T. portulacastrum showed the presence of alkaloids, tannins, flavonoids, and tri-terpenoids. In fatty acid composition analysis, both bound fatty acids and free fatty acids were isolated from n-hexane extract that showed the presence of the highest percentage of palmitoleic acid (67.095% and 48.843%, respectively) and stearic acid (12.14% and 20.437%, respectively). Dichloromethane and methanol extracts were found to be cytotoxic on HeLa cells in cytotoxicity assay against Vero, HeLa, and BHK-21 cell lines. The highest phenolic content was observed in ethyl acetate extract (68.55±0.038 mg/g) and the highest flavonoid content was found in chloroform extract (477.01±0.104 mg/g). The DCM fraction revealed the highest total antioxidant capacity (284.99±0.113 mg/g), and the IC50 value for ethyl acetate extract was the lowest (110.35±0.160 μg/ml) of all the extracts. Dhaka Univ. J. Pharm. Sci. 21(1): 33-43, 2022 (June)